Weed management in RR® maize with herbicides applied isolated or associated with glyphosate - Basso, Felipe José Menin; Galon, Leandro; Forte, César Tiago; Agazzi, Luciane Renata; Nonemacher, Felipe; Perin, Gismael Francisco; Fiabani, Renan Carlos; Winter, Fábio Luís (Revista de Ciências Agroveterinárias, 2018)
The objective of this work was to evaluate the effectiveness, selectivity and effect on yield components of RR® maize as a function of herbicide application, applied alone or in a tank mix. The experiment was conducted in a randomized block design, with four replications, and treatments were control without weeding, control with weeding, glyphosate, glyphosate + [atrazine+simazine], glyphosate + [atrazine + simazine], glyphosate + tembotrione, glyphosate+mesotrione, T8-glyphosate + nicosulfuron, glyphosate + 2,4-D, glyphosate + [atrazine + S-metolachlor], T11-glyphosate + (atrazine + S-metolachlor), glyphosate + S-metolachlor, glufosinate ammonium, [nicosulfuron + mesotrione], glyphosate + [nicosulfuron + mesotrione] and glyphosate + [nicosulfuron+mesotrione] + [atrazine + simazine]. Herbicide phytotoxicity to a SYN Supremo VIP3 maize hybrid and control of Urochloa plantaginea and Digitaria ciliaris were evaluated at 7, 14, 21 and 28 days after treatment application. Prior to crop harvest, we determined weed control and, in ten plants per experimental unit, the variables related to grain yield components such as ear insertion height, ear length, number of rows and grains per rows on the ears of corn. During harvest, the mass of one thousand grains and yield were evaluated. It was observed that all herbicide treatments caused low phytotoxicity in maize, except for the post-emergence tank mix composed of glyphosate + 2,4-D and glyphosate + mesotrione, that showed the highest injuries in the four evaluated periods. Most of the herbicides showed good control of D. ciliaris and U. plantaginea, except for the pre-harvest mixture of glyphosate + 2,4-D. The post-emergence glyphosate + [atrazine + simazine] tank mix demonstrated the highest grain yield. It can be concluded, therefore, that depending on the association of herbicides, synergistic effect occurs for both weed control and crop phytotoxicity, being productivity being the main influenced variable.